2004
DOI: 10.1038/sj.onc.1208000
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis reveals differential gene expression patterns and regulation of single target genes contributing to the opposing phenotype of TrkA- and TrkB-expressing neuroblastomas

Abstract: Expression of neurotrophin receptors of the tyrosine kinase receptor (Trk) family is an important prognostic factor in solid tumors including neuroblastoma. High expression of TrkA (NTRK1) is associated with a favorable biology and outcome of neuroblastoma, whereas TrkB (NTRK2) is expressed on aggressive neuroblastomas with unfavorable outcome. To gain new insights into the global gene expression program resulting in these divergent biological phenotypes, we stably expressed either TrkA or TrkB in the human SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 41 publications
4
60
0
1
Order By: Relevance
“…rGal-1 alone was not sufficient to induce the full invasive capacity of SY5Y-TrkB cells, suggesting that other BDNF-induced factors are involved in invasion as well. We and others have previously suggested MCSP and c-Met as TrkB-regulated, proinvasive factors in NB (Hecht et al, 2005;Schulte et al, 2005). Our current findings identify Gal-1 as a third player contributing to TrkB-mediated invasiveness in NB.…”
Section: Discussionsupporting
confidence: 71%
“…rGal-1 alone was not sufficient to induce the full invasive capacity of SY5Y-TrkB cells, suggesting that other BDNF-induced factors are involved in invasion as well. We and others have previously suggested MCSP and c-Met as TrkB-regulated, proinvasive factors in NB (Hecht et al, 2005;Schulte et al, 2005). Our current findings identify Gal-1 as a third player contributing to TrkB-mediated invasiveness in NB.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, TrkA may signal to p53 in other ways, because it can bind both p53 and c-Abl, a p53 activator (55)(56)(57), and promote the deacetylation of p53 in PC12 cells (58). It is likely that the modulation of p53 and Bcl-2 levels by TrkA occurs at the post-transcriptional level, because several recent cDNA expression profiling studies on NB tumors or SH-SY5Y NB cells stably transfected with TrkA did not report changes in p53 or Bcl-2 genes expression (59,60). We are currently characterizing the TrkA signals that lead to enhanced p53 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although these stress-activated kinases have been shown to contribute to apoptotic cell death, by upregulating proapoptotic BH3-only Bcl-2 family members (e.g., Whitfield et al 80 ), BDNF is unlikely to modulate this death pathway under the experimental conditions used in this work. Recent studies have shown that activation of TrkB receptors elicits a complex program of changes in gene expression, 81 which will cause multiple changes in the proteome. Therefore, in addition to Bcl-2, other proteins are likely to contribute to neuroprotection by BDNF under excitotoxic conditions.…”
mentioning
confidence: 99%